2004
DOI: 10.1007/s00253-004-1626-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of mineral medium for growth of Actinomadura sp. ATCC 39727, producer of the glycopeptide A40926: effects of calcium ions and nitrogen sources

Abstract: Actinomadura sp. ATCC 39727 produces the glycopeptide antibiotic A40926, structurally similar to teicoplanin, with significant activity against Neisseria gonorrhoeae and precursor of the semi-synthetic antibiotic dalbavancin. In this study the production of A40926 by Actinomadura under a variety of growth conditions was investigated. The use of chemically defined mineral media allowed us to analyze the influence of carbon and nitrogen sources, phosphate, ammonium and calcium on the growth and the antibiotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Up-regulation of cluster 15 may be part of this strategy because tabtoxin-like β-lactams inhibit the glutamine synthetase of organisms competing for ammonium. The strict interplay between nitrogen and secondary metabolism is in agreement with previous data 7, 41, 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Up-regulation of cluster 15 may be part of this strategy because tabtoxin-like β-lactams inhibit the glutamine synthetase of organisms competing for ammonium. The strict interplay between nitrogen and secondary metabolism is in agreement with previous data 7, 41, 42 .…”
Section: Discussionsupporting
confidence: 92%
“…In particular, Gunnarsson et al (12) found that low initial phosphate concentrations were beneficial for A40926 production and that the onset of production was not governed by the residual phosphate concentration, although its level strongly influenced production rates and final titers. These results were independently confirmed by Technikova-Dobrova et al (42). The molecular bases for phosphate regulation of A40926 production have not yet been studied.…”
mentioning
confidence: 63%
“…Other StrR-like regulators have been characterized, such as NovG from the Streptomyces caeruleus novobiocin cluster (10), CloG from the Streptomyces roseochromogenes clorobiocin cluster (10), and KasT from the Streptomyces kasugaensis kasugamycin cluster (13). Recently, the production of A40926 was found to be influenced by phosphate (12,42). In particular, Gunnarsson et al (12) found that low initial phosphate concentrations were beneficial for A40926 production and that the onset of production was not governed by the residual phosphate concentration, although its level strongly influenced production rates and final titers.…”
mentioning
confidence: 99%
“…Yeast-starch medium was used for growth, and culture conditions were as reported previously (36). S. lividans strains 1326 (wild type), KO-421 (relC), and KO-422 (relC rif1) used in this study were described previously (18,20).…”
mentioning
confidence: 99%